KAJIAN PEMANFAATAN MIKROTIK SEBAGAI USER MANEJER MENGGANTIKAN CHILISPOT DI UNIVERSITAS NEGERI PAPUA (STUDI KASUS : GEDUNG TEKNIK): STUDY OF THE UTILIZATION OF MICROTIK AS A USER MANEGER TO REPLACE CHILISPOT AT PAPUA STATE UNIVERSITY (CASE STUDY: TECHNICAL BUILDING) - Alex De Kweldju (JISTECH: Journal of Information Science and Technology, 2014)
Universitas Negeri Papua’s (UNIPA) Internet network use Chilispot and RADIUS Server as User Manager application to control user to use internet facility. In Chilispot –at client side- implementation, user was used to complain about login process after a power outage that usually happens in UNIPA. When the power outage happened, user status in database was still noted online cause user couldn’t login again after power back. User has to report to Computer Center or waited for online status restore. Router Mikrotik is multifunction device that has User Manager feature. User Manager in Mikrotik can handle userlogin without affected by power outage because it use different procedure from Chilispot. User can directly access internet again without login process after power outage. In this research, author replaced Chilispot at Engineering Building with Mikrotik User Manager to find out Mikrotik capability in solve Chilispot problem. After one mount implementation, internet users at Engineering Building didn’t report any problem related to internet access after power outage. Mikrotik User Manager allows user to login once every three days that simplify internet access process.